2013
DOI: 10.1098/rspb.2013.1605
|View full text |Cite
|
Sign up to set email alerts
|

Sexual selection explains more functional variation in the mammalian major histocompatibility complex than parasitism

Abstract: Understanding drivers of genetic diversity at the major histocompatibility complex (MHC) is vitally important for predicting how vertebrate immune defence might respond to future selection pressures and for preserving immunogenetic diversity in declining populations. Parasite-mediated selection is believed to be the major selective force generating MHC polymorphism, and while MHC-based mating preferences also exist for multiple species including humans, the general importance of mate choice is debated. To inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
73
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 76 publications
(117 reference statements)
1
73
0
Order By: Relevance
“…HLA class 1 molecules have also been shown to have a role in both neurodevelopment (29) and mate selection (30). It is thus possible that HLA-B27 has a selective developmental or reproductive advantage that maintains its prevalence in multiple human populations despite the almost certain evolutionary disadvantages associated with increased SpA prevalence.…”
Section: Other Functions Of Hla-b27 Heterotrimers and Free Heavy Chainsmentioning
confidence: 99%
“…HLA class 1 molecules have also been shown to have a role in both neurodevelopment (29) and mate selection (30). It is thus possible that HLA-B27 has a selective developmental or reproductive advantage that maintains its prevalence in multiple human populations despite the almost certain evolutionary disadvantages associated with increased SpA prevalence.…”
Section: Other Functions Of Hla-b27 Heterotrimers and Free Heavy Chainsmentioning
confidence: 99%
“…A recent comparative and meta‐analysis even suggests that sexual selection may contribute more to the maintenance of MHC variation than pathogens (Winternitz et al . ). The association of MHC genes with sexual selection is typically explained through a couple of ultimate mechanisms.…”
Section: Introductionmentioning
confidence: 97%
“…MHC molecules are membrane receptors that, according to the current paradigm, present peptides of intracellular (MHC class I) or extracellular (MHC class II) origin to immune-surveillance-dedicated cells such as T lymphocytes6. As a consequence, an individual’s ability to recognize and resist a broad spectrum of potential pathogens tends to correlate with the diversity of its MHC alleles89 (but see the study by Milinski10). In this context, the evolutionary benefits of MHC-dependent mate choice are straightforward: choosy individuals preferring MHC-dissimilar mates are expected to produce offspring with higher fitness.…”
mentioning
confidence: 99%
“…In fact, various studies found that MHC-dependent mate choice had a positive effect on parasite load and survival rates of juveniles1112 and also ultimately on offspring fitness13. Except for some recently published cases of MHC-assortative choice1415, MHC-disassortative mate choice has been found in many vertebrate species, including fish1116, reptiles17, birds18 and mammals4919.…”
mentioning
confidence: 99%